1995
DOI: 10.2307/4002507
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Rangeland Management Strategies under Rainfall and Price Risks

Abstract: Dynamic programming was used to obtain optimal management and marketing policies for stocker operations in Southeastern Colorado under different stocking rates, rainfall, and price scenarios. Simulated steer liveweights at low, moderate, and high stocking rates were incorporated with simulated steer prices to masimize the present value of net returns from the sale of 0,50, and 100% of the steer inventory in July, August, September, or October. Two low-risk, 1 moderate-risk, and 2 high-risk scenarios were consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Farm management models useful for integrated land-use modeling must simulate interrelated farm management choices, primarily selection of crops and rotations, and also choices of input levels and production technologies. Mathematical programming models for typical Great Plains farm and ranch types have been developed (Burt and Allison 1963, Carrande 1992, Young et al 1982. More recently, using a method called discrete, stochastic sequential programming (Rae 1971), Young and colleagues modeled crop and technology choice and water use on lands irrigated from the Ogallala Aquifer in eastern Colorado.…”
Section: Models Of Farm and Ranch Management The Land-use Inputs Necmentioning
confidence: 99%
“…Farm management models useful for integrated land-use modeling must simulate interrelated farm management choices, primarily selection of crops and rotations, and also choices of input levels and production technologies. Mathematical programming models for typical Great Plains farm and ranch types have been developed (Burt and Allison 1963, Carrande 1992, Young et al 1982. More recently, using a method called discrete, stochastic sequential programming (Rae 1971), Young and colleagues modeled crop and technology choice and water use on lands irrigated from the Ogallala Aquifer in eastern Colorado.…”
Section: Models Of Farm and Ranch Management The Land-use Inputs Necmentioning
confidence: 99%
“…However, Behnke et al (1993) and Scoones (1994), in African savannas, found that grazing management utilizing high stocking rates annually adjusted to forage productivity variation showed the highest economic benefits. Carande et al (1995) suggested that high stocking rates can give better economic results than moderate or low stocking rates only in environments with a low risk of drought occurrences. Therefore, because droughts are frequent in arid and semiarid regions (Noy-Meir 1973), high stocking rates would not be recommended.…”
Section: Grazing Strategy and Economic Resultsmentioning
confidence: 99%
“…The rancher has to cope with a highly variable and unpredictable inter-annual rainfall (Walker et al, 1981;Pickup and Stafford Smith, 1993), which is the primary determinant of rangeland productivity (Fynn and O'Connor, 2000), and meat price fluctuations, which are caused by global market fluctuations (Campbell et al, 2006;Gross et al, 2006). Under these conditions, it is widely accepted that range management should aim at robustness and adaptability (Carande et al, 1995;Berkes et al, 2000;Vetter, 2005). Robustness measures the ability of the management actions to maintain the system in desired conditions, despite uncertain environment (Anderies et al, , 2013Roug茅 et al, 2013).…”
Section: Introductionmentioning
confidence: 99%